Synthesis and Characterization of Poly[thiadiazoledithiocarbamate] and Some Metal Complexes - El-Shekeil, Ali; Al-Karbooly, Ashour; Al-Yusufy, Fatma (Springer Nature, 2001)
Poly[thiadiazoledithiocarbamate] (PTDTC) is prepared from the reaction of 2-amino-5-mercapto-1,3,4-thiadiazole with carbon disulfide followed by in situ removal of hydrogen sulfide gas. Three polymer-metal complexes of cobalt, copper and lead are prepared from the reaction of PTDTC with the metal salts in DMSO. The polymer-metal complexes are investigated by elemental analysis, electronic spectra, Fourier Transform infrared spectroscopy and magnetic susceptibility. The DC electrical conductivity variation with temperature in the range 300-500 K of the annealed polymer, the 5% I2 doped polymer and the polymer-copper complex is determined for comparison. All the polymer-metal complexes are high melting, thermally stable materials that are insoluble in most common organic solvents.